Understanding Repurchase Intentions in Dental Care: The Mediating Role of Regret and Service Factors - Ryan Tegar Pamungkas; Ujang Sumarwan; Megawati Simanjuntak (Binus Business Review, 2025)
In the competitive dental healthcare market of Balikpapan, Indonesia, retaining customers is a critical challenge due to rising competition and increasing awareness of oral health, with 56.9% of the population experiencing dental issues and 80.7% seeking professional care. The research aimed to investigate the determinants of repurchase intention in dental clinic services, focusing on customer expectation, customer experience, service quality, service personalization, and alternative attractiveness, with customer regret as a mediating variable. Using a quantitative approach, data were collected from 255 dental clinic customers in Balikpapan via an online questionnaire, selected through purposive sampling. Structural Equation Modeling with Partial Least Squares (SEM-PLS) analysis was employed to test the relationships. Results show that customer expectation, customer experience, service quality, and service personalization significantly reduce customer regret, which, in turn, positively influences repurchase intention. Conversely, alternative attractiveness increases regret, negatively impacting repurchase intention. Customer regret significantly mediates these relationships, highlighting its critical role in shaping customer loyalty. The findings contribute to regret theory by demonstrating its application in dental healthcare and offer practical strategies for clinics to enhance loyalty. These strategies include improving service quality, leveraging technology for personalization, managing expectations effectively, and countering alternative attractiveness through unique value propositions. The research provides actionable insights for dental clinics in Balikpapan to foster customer retention in a competitive market.